2018
DOI: 10.1002/rcs.1958
|View full text |Cite
|
Sign up to set email alerts
|

A novel augmented reality (AR) scheme for knee replacement surgery by considering cutting error accuracy

Abstract: The proposed system is focused on overlaying only the remaining areas of surgery that need to be completed. Finally, this study solves the issues of navigation with AR when cutting bones in a scheduled direction and depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…This part of the research presents features (highlighted by blue dashed lines in Figure ) and limitations (highlighted by red dashed lines) of the best current system. The aim of this research is to reduce the cutting error in jaw surgery, for which we found a solution in the work of Pokhrel et al who achieved high accuracy in cutting in hard‐tissue during knee surgery. Pokhrel et al enhanced the ICP with a VSA to estimate the shape and provide a better view of target areas in narrow surgical corridors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…This part of the research presents features (highlighted by blue dashed lines in Figure ) and limitations (highlighted by red dashed lines) of the best current system. The aim of this research is to reduce the cutting error in jaw surgery, for which we found a solution in the work of Pokhrel et al who achieved high accuracy in cutting in hard‐tissue during knee surgery. Pokhrel et al enhanced the ICP with a VSA to estimate the shape and provide a better view of target areas in narrow surgical corridors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The aim of this research is to reduce the cutting error in jaw surgery, for which we found a solution in the work of Pokhrel et al who achieved high accuracy in cutting in hard‐tissue during knee surgery. Pokhrel et al enhanced the ICP with a VSA to estimate the shape and provide a better view of target areas in narrow surgical corridors. The enhanced ICP algorithm has reduced the cutting error by 1 mm and increased the accuracy of 0.40 to 0.55 mm while decreased the processing time to 9‐10 fps.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This solution provided the accuracy in terms of overlay error 0.30 to 0.40 mm and processing time by 7 to 10 frames per second. Pokhrel et al have conducted research to downgrade the cutting error of the surgery. They implemented volume substraction method to find out the remaining area to be cut in the operation.…”
Section: Introductionmentioning
confidence: 99%